Penerapan Manajemen Kelas sebagai Upaya dalam Meningkatkan Efektivitas Pembelajaran PAI - Husna Amalia (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2017)
Classroom management is a part of main component from professional teacher. The concept of classroom management has aim to give problem solving toward class difficulties that doesn’t limit on subject matter but also all of the component in managing class. The concept of classroom management effort to improve class excellence as well as possible for supporting the proccess of educative interraction to achieve the aim of effective learning especially for Islamic Education subject. Therefore this case must be supported by professional teacher in managing class well